Enhanced photocatalytic activity of CoNi-decorated Zn-doped Cu2O synthesized by electrodeposition technique. Issue 4 (23rd January 2023) - Budi, Setia; Sutrisno, Mega Gladiani; Pratiwi, Yussi; Yusmaniar
Abstract : The Zn-doped Cu2 O crystals were decorated with CoNi cocatalyst using electrodeposition technique. This approach successfully enhanced the photocatalytic activity and photostability of the photocatalyst. Abstract : Cu2 O is known as a potential photocatalyst that functions in the visible light region due to its narrow bandgap energy. In this study, to improve photocatalytic activity and photostability, Zn-doped Cu2 O was decorated with CoNi cocatalyst using an electrodeposition technique at different deposition times. Photocatalytic activity of the CoNi-decorated Zn-doped Cu2 O was investigated in the degradation of methylene blue (MB) dye, which is known as a toxic, mutagenic, and carcinogenic synthetic dye. The CoNi cocatalyst was found to effectively increase the photoelectrochemical properties and photocatalytic activity of Zn-doped Cu2 O. Electrochemical impedance spectroscopy measurements show that by growing CoNi, the charge transfer resistance of the Zn-doped Cu2 O decreased from 3.23 kΩ to 1.11 kΩ. A high photocurrent, measured under simulated solar irradiation using a linear sweep voltammetry technique, of 25.43 mA cm −2 was obtained with a CoNi deposition time of 150 s. The CoNi-decorated Zn-doped Cu2 O demonstrated a high photostability and photocatalytic activity, as shown by the increase of MB photodegradation from 26.03% to 71.55%. The growth of CoNi cocatalyst is believed to have enhanced carrier concentration, charge transfer, and charge carrier lifetime, thus increasing the photocatalytic activity of the Zn-doped Cu2 O.